Correlation of open-circuit voltage and energy levels in zinc-phthalocyanine: C₆₀ bulk heterojunction solar cells with varied mixing ratio - Tietze, M; Tress, W; Pfützner, S; Schünemann, C; Burtone, L; Riede, M; Leo, K; Vandewal, K; Olthof, S; Schulz, P; Kahn, A (American Physical Society, 2013)
The maximum open-circuit voltage VOC of bulk-heterojunction solar cells is limited by the effective HOMO(donor)-LUMO(acceptor) gap of the photoactive absorber blend. We investigate blend layers comprising zinc-phthalocyanine (ZnPc) and the buckminster fullerene C60 with ultraviolet, x-ray, and inverse photoelectron spectroscopy. By varying the volume mixing ratio ZnPc:C60 from 6:1 to 1:6, we observe a linear increase of the HOMO(ZnPc)-LUMO(C60) gap by 0.25 eV. The trend in this gap correlates with the change in the charge transfer energy measured by Fourier-transform photocurrent spectroscopy as well as with the observed open-circuit voltage of solar cells containing ZnPc:C60 as the photoactive absorber layer. Furthermore, the morphology of different ZnPc:C60 blend layers is investigated by grazing-incidence x-ray diffraction. As physical origins for the changed energy levels, a suppressed crystallization of the C60 phase in the presence of donor molecules as well as concentration-dependent growth modes of the ZnPc phase are suggested. © 2013 American Physical Society.